2009
DOI: 10.1103/physreva.79.033848
|View full text |Cite
|
Sign up to set email alerts
|

Subwavelength atom localization via coherent manipulation of the Raman gain process

Abstract: We present a simple scheme of atom localization in a subwavelength domain via manipulation of Raman gain process. We consider a four-level system with a pump and a weak probe field. In addition, we apply a coherent field to control the gain process. The system is similar to the one used by Agarwal and Dasgupta ͓Phys. Rev. A 70, 023802 ͑2004͔͒ for the superluminal pulse propagation through Raman gain medium. For atom localization, we consider both pump and control fields to be the standing-wave fields of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
63
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 21 publications
1
63
0
Order By: Relevance
“…Instead of the measurement of the population in the upper state, Agarwal and Kapale put forward a scheme of atom localization via the measurement of the population of one of the ground states, which led to only two localization peaks in a unit wavelength region [27]. More recently, unique position information of the atom can be obtained via coherent manipulation of the Raman gain process [28] and Raman-driven coherence [29]. On the other hand, the behaviors of two-dimensional (2D) atom localization in multi-level atomic systems also have been studied in recent years because of its unique properties and extensive applications.…”
Section: Introductionmentioning
confidence: 98%
“…Instead of the measurement of the population in the upper state, Agarwal and Kapale put forward a scheme of atom localization via the measurement of the population of one of the ground states, which led to only two localization peaks in a unit wavelength region [27]. More recently, unique position information of the atom can be obtained via coherent manipulation of the Raman gain process [28] and Raman-driven coherence [29]. On the other hand, the behaviors of two-dimensional (2D) atom localization in multi-level atomic systems also have been studied in recent years because of its unique properties and extensive applications.…”
Section: Introductionmentioning
confidence: 98%
“…Several simple localization schemes have been proposed using such as the resonance fluorescence in a two-level system, the measurement of Autler-Townes split spontaneous emission in a three-level system, and a three-level -type atom interacting with a classical standing-wave field and a weak probe field [4][5][6]. Furthermore, one-dimensional (1D) atom localization can be achieved in Raman gain atoms [7], and coherent population trapping [8][9][10]. There will be more practical application in two-dimensional (2D) atom localization [11,12], and hence many works have been put forward.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that control of the amplitudes of the driving field provided a strong narrowing line that yielded a better resolution in position measurement of the single atom. In the scheme[12] , a parity violation was considered, and a high field was required to break this violation.In 2009, two different systems were used for the atom localizations [13,14] to observe single position measurement. In the system [13] , a four-level Raman gain process was used for subwavlength atom localization and a single peak was observed for an atom.…”
mentioning
confidence: 99%
“…In 2009, two different systems were used for the atom localizations [13,14] to observe single position measurement. In the system [13] , a four-level Raman gain process was used for subwavlength atom localization and a single peak was observed for an atom.…”
mentioning
confidence: 99%
See 1 more Smart Citation